2020
DOI: 10.1039/c9ta13719j
|View full text |Cite
|
Sign up to set email alerts
|

A novel 2D perovskite as surface “patches” for efficient flexible perovskite solar cells

Abstract: High-efficiency flexible perovskite solar cells based on a novel mixed-cation 2D perovskite passivating FA-based perovskite absorber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“… 22 The work by Yangi et al also reported the formation of mixed-2D perovskites with cations of phenylformamidinium (PFA). 119 We also discovered that bifunctional PTABr post-treatment to CsPbI 3 can further improve the phase stability by gradient Br doping and the PCE can reach 17.06%. 120 Furthermore, PTACl treatment to CsPbI 3 can passivate the surface traps effectively and boost the PCE to more than 19%.…”
Section: Steric Hindrance Stabilizationmentioning
confidence: 81%
“… 22 The work by Yangi et al also reported the formation of mixed-2D perovskites with cations of phenylformamidinium (PFA). 119 We also discovered that bifunctional PTABr post-treatment to CsPbI 3 can further improve the phase stability by gradient Br doping and the PCE can reach 17.06%. 120 Furthermore, PTACl treatment to CsPbI 3 can passivate the surface traps effectively and boost the PCE to more than 19%.…”
Section: Steric Hindrance Stabilizationmentioning
confidence: 81%
“…While formamidinium cations are better due to their attenuated band gaps and stability, the mixed cation 2D perovskites show excellent performance both in terms of device improvement and in terms of thermal stability. This performance is achieved as a result of the enhancement of surface flaws and avoiding the rearrangement of the hole transfer layer and perovskites layer at adjacent surface edges [ 34 ]. The nonlinear scattering and photocarrier recombination are comparatively reduced in ultrathin 2D perovskites, which is favorable for the investigation of intrinsic optical properties [ 35 ].…”
Section: D Nanomaterials For Energy Scavenging Devicesmentioning
confidence: 99%
“…[5][6][7] This lower PCE can be partially attributed to the lower transmittance and the higher sheet resistance of PET/ITO substrates in comparison with conductive glasses. 8 More importantly, the issues of the perovskite crystal growth and the cracking of perovskite grains, which determines the photovoltaic performance of PSCs, are also severely restricted by a exible substrate because the deformation of exible substrates is usually inevitable under the annealing process. 4,9 Except for photovoltaic performance, the mechanical stability of exible PSCs is severely affected by the fragility of ITO as well as the perovskite crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been devoted to improve the efficiency and stability of the exible PSCs. In terms of efficiency improvement, Yangi et al reported that a novel two-dimension (2D) phenylformamidinium iodide (PFAI) cation as surface "patches" for stable exible PSCs with the PCE of 19.89%, 8 while some other groups reported a new concept of porous planar or nanopillar arrays as an electron transport layer, achieving a PCE over 20%. [10][11][12] In terms of stability improvement, a bio-inspired vertebral design, a so fullerene network and 2D perovskite as surface patches have been developed to enhance the mechanical stability of exible PSCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation